PREVALENCE OF SLEEP DISORDERS IN STUDENTS AFFECTING THEIR MENTAL STATE - Mittal , Ashish Kumar (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: Sleep is an essential part of human homeostasis. Sleep disorders are closely linked to serious medical, psychological, and social problems. Chronic sleep deprivation is becoming more of a problem in many countries. Because the body’s stress systems are critical in adapting to a constantly changing and uncertain environment, it is critical to determine whether insufficient sleep affects these systems. In an adaptive ability to preserve homeostasis, the human body activates defensive systems. Insomnia may arise if these defences fail. Material and Method: The cross-sectional type of survey study was conducted to analyse the sleeping pattern. Among the various age group of students, mostly college going students were choose as they experience more pressure and disturbance in their sleep because of various reasons including academic pressure. The sampling census was done with 200 students from different academic year. Result: Out of 200 students, the ratio was higher on girls as on boys. 58% of girls were present in the survey where only 42% of boys were present. The average age of participants was around 22 years, where most of them were staying in hostels. The survey questioner included some of the questions related to eating and addiction habits in which smokers and drinkers were found around 15% of targeted audience. While as one having psychological disorders were found around 36%. More than 33% of the participants were found struggling with sleeping disorder. Conclusion: our findings suggest that a large proportion of college students are at risk for sleep disorders or poor sleep hygiene, and that sleep may have an influence on academic performance. Student retention and graduation rates are a concern for higher education institutions. According to this study, medical students have a significant frequency of sleep disorders Keywords: Sleep disorder, defensive systems, Insomnia, mental state